HPA Axis‐Rhythms. Issue 3 (12th June 2014) - Spiga, Francesca; Walker, Jamie J.; Terry, John R.; Lightman, Stafford L.
Abstract: The hypothalamic‐pituitary‐adrenal (HPA) axis regulates circulating levels of glucocorticoid hormones, and is the major neuroendocrine system in mammals that provides a rapid response and defense against stress. Under basal (i.e., unstressed) conditions, glucocorticoids are released with a pronounced circadian rhythm, characterized by peak levels of glucocorticoids during the active phase, that is daytime in humans and nighttime in nocturnal animals such as mice and rats. When studied in more detail, it becomes clear that the circadian rhythm of the HPA axis is characterized by a pulsatile release of glucocorticoids from the adrenal gland that results in rapid ultradian oscillations of hormone levels both in the blood and within target tissues, including the brain. In this review, we discuss the regulation of these circadian and ultradian HPA rhythms, how these rhythms change in health and disease, and how they affect the physiology and behavior of the organism. © 2014 American Physiological Society. Compr Physiol 4:1273‐1298, 2014.